The place of intersubjective recognition and its influence in the construction of senses of authority in education (Research, Society and Development, 2022)
From the finding of a paradoxical condition and a crisis of authority in Education, with the effects of valuing the school, teachers and students, it is intended to approach the place of intersubjective recognition (Honneth, 2005) in today's society and to ponder the importance of a type of authority manifested by the psychological need for stability and security that emerges in social relations by mutual recognition,  in a sense of social belonging. For this task, the school's need to resist market influences that seem to stimulate a state of denial or forgetfulness about the importance of the social dimension of recognition in a growing movement of "dedemocratization" is contextualized as a backdrop. We conclude, in the mode of a theoretical essay, that it can be fruitful the emergence of new studies on the meanings of authority of young people in high school, through the bias of reciprocal intersubjective recognition, in order to dialogue with other studies that also seek to better understand the dynamics of conflicts in school and the elements that sustain this possible state of crisis in Education.